2021
DOI: 10.3808/jeil.202100067
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Characteristics of Soil Moisture in the Three Rivers Headwaters Region, China

Abstract: The change of soil moisture has significant influence on the surface energy distribution and evapotranspiration process and causes the climatic environment changes. It is thus urgent to detect soil moisture facing climate change problems. Based on apparent thermal inertia method, the GLDAS soil moisture of the layer in 0 ~ 10 cm, 10 ~ 40 cm, 40 ~ 100 cm, 100 ~ 200 cm under the ground surface are proceeded for downscaling and the monthly soil moisture are obtained by combination of MODIS data. Statistics of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Based on observation under the simulated warming conditions in the Chengduo station in TRHR, the soil temperature increased by 2.50 ℃ and 1.36 ℃ at the soil depth of 0-15 cm and 15-30 cm, respectively, while the soil water decreased by 0.07% and 0.09% at the soil depth of 0-15 cm and 15-30 cm, respectively (Yao et al, 2019). Cao and Jin (2021) also concluded that soil water is negatively correlated with air temperature and positively correlated with precipitation.…”
Section: Influencing Factors On Soil Water Sources In Different Ablat...mentioning
confidence: 98%
See 1 more Smart Citation
“…Based on observation under the simulated warming conditions in the Chengduo station in TRHR, the soil temperature increased by 2.50 ℃ and 1.36 ℃ at the soil depth of 0-15 cm and 15-30 cm, respectively, while the soil water decreased by 0.07% and 0.09% at the soil depth of 0-15 cm and 15-30 cm, respectively (Yao et al, 2019). Cao and Jin (2021) also concluded that soil water is negatively correlated with air temperature and positively correlated with precipitation.…”
Section: Influencing Factors On Soil Water Sources In Different Ablat...mentioning
confidence: 98%
“…Soil water has also been deeply concerned in TRHR. Cao and Jin (2021) analyzed the distribution characteristics of soil water and its relationship with temperature and precipitation in TRHR. The influence of precipitation on soil water in the alpine steppe was greater than that in an alpine meadow, especially in lower-altitude areas (Li et al, 2022) annual mean soil surface temperature by 0.8 °C under climate warming in the sources region of the Yangtze river (Xue et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of the suitability of land space development refers to the suitability of land space for different development and utilization methods, such as urban construction and agricultural production. It is supposed to evaluate the suitability of the land space for urban construction and agricultural production on the basis of evaluating the carrying capacity of resources and environment [3]. The concept of carrying capacity originated in ancient Greece and was originally defined as "the maximum number of organisms that can survive under certain resource and environmental conditions".…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the sustained and rapid development of China's economy and society has caused dislocation and imbalance in the water resources of some regions. It is urgent to take into account the regional water resources occurrence conditions and development-utilization needs in territorial and spatial planning, and to comprehensively ensure that regional economic, social, ecological and other development goals fully adhere to the principle of "determining the city by water, determining the land by water, determining the people by water, and determining the production by water", and constantly strengthen the rigid constraints of water resources [3,4]. It is of great significance to strengthen the rigid constraints of water resources in national land space planning.…”
Section: Introductionmentioning
confidence: 99%